Making the most of the European Fiscal Board - Zareh Asatryan; Xavier Debrun; Friedrich Heinemann; Michal Horvath; Ľudovít Ódor; Mustafa Yeter (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2017)
Following numerous reforms of fiscal governance in the eurozone since 2011, the year 2016 saw another important innovation: the founding of the European Fiscal Board (EFB) with the selection and appointment of its five members. The EFB was one of the elements envisaged by the Five Presidents' Report in June 2015 (Juncker et al., 2015) for a future "Fiscal Union". It is the only element among those in the report to have been established within such a remarkably short time span. The decision to create this new institution was taken by the European Commission (EC) in October 2015. The Board began operating shortly after its members were appointed in October 2016.
Keywords: 330